(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The primary purpose of the study is to evaluate the mediating effect of organisational reputation while determining the relationship between employee branding and MNCs competitive advantage. Method/ Design: The study has adopted a quantitative research design involving the survey results collected from 387 MNCs. The SEM technique has been utilised in order to execute the confirmatory analysis along with the path analysis. Findings: Findings reveals that there is a significant and positive relationship between organisational reputation, employee branding and competitive. The findings confirmed that organisational reputation partially mediates the relationship between employee branding and competitive advantage. Limitation: The findings are purely based on the MNCs operating within the IT sector of Malaysia. However, the findings may deviate when if applied to other sector or country.